The Impact of SARS-CoV-2 Infection on Sleep, Daytime Sleepiness, and Depression—Longitudinal Cohort Study - Klāvs Putenis; Sintija Strautmane; Madara Mičule; Evelīna Kočāne; Guntis Karelis (Medicina, 2024)
Background and Objectives: COVID-19 disease, caused by the SARS-CoV-2 virus, has presented significant challenges to global health, with acute and chronic implications for various aspects of well-being, including sleep and quality of life. This study aimed to investigate the impact of SARS-CoV-2 infection on sleep quality, daytime sleepiness, and quality of life in hospitalised and home-treated patients after three and six months. Materials and Methods: A longitudinal cohort study was conducted, enrolling hospitalised patients from a single clinical university hospital and home-treated participants through a survey spread through social networks. Individuals who had tested positive for the SARS-CoV-2 virus in the past three months and had a symptomatic course of the disease were included in the study. Participants with previously diagnosed sleep disorders were excluded from the study. Participants were evaluated using internationally validated self-evaluation scales, including the Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), Patient Health Questionnaire-9 (PHQ-9) and Fatigue Severity Scale (FSS). Data were collected three and six months after laboratory-confirmed SARS-CoV-2 infection, with informed consent obtained from all participants. Statistical analysis was performed using the Wilcoxon signed rank test, Fisher–Freeman–Halton exact, Pearson Chi tests and Spearman correlation. Results were considered statistically significant with p value < 0.05. Results: In total, 66 participants with a mean age of 44.05 ± 21.61 years were enrolled in the study. Most patients (n = 36) were treated at home and 30 at hospital. Six months after SARS-CoV-2 infection, home-treated patients reported a higher prevalence of poor sleep quality (52.8%, n = 19, p = 0.015, PSQI) and hospitalised patients showed a lower prevalence of depressive symptoms (p < 0.001, PHQ-9) as 90% (n = 27) had minimal or no symptoms compared to 30.6% (n = 11) in a home-treated group. Conclusions: These findings mark the importance of the COVID-19 patients’ management settings as people treated at home had worse sleep quality and more depressive symptoms six months after infection indicating worse life quality.